The Position of Kejawen in the Indonesian Constitution - Kristina, Ayu (DINIKA : Academic Journal of Islamic Studies, 2021)
The paradigms of world religions often influence Indonesia's general understanding of religion. Indigenous religious practices are often labeled as animistic practices. The adherents of the Indigenous religion are often regarded as worshipers of trees, mountains, and the like. Such is the case with adherents of the Indigenous religion in Java Island (Kejawen). From the results of a literature study that utilizes various literature and paradigms related to the existence of religion in Indonesia, this study tries to look further into the position of Kejawen in the Indonesian constitution. The results of this study found that Kejawen adherents still experience many discriminatory actions due to the lack of comprehensive understanding of the Indonesian people regarding the importance of symbolic recognition and the resources of Kejawen teachings. In addition, Kejawen adherents also feel they have a historical burden because they are not considered adherents of a religion "recognized" by the State. Kejawen is often associated with occult and shamanic traditions. The Indonesian constitution clearly states that the State must be fair in guaranteeing and giving freedom to every citizen to choose, adhere to, and practice their religions or beliefs. Kejawen, as part of the Indigenous religion, should also be protected and guaranteed its rights and freedoms and placed in an equal position with other religions.